Let’s talk about weight - Tammy McCausland (The Journal of Health Design, 2021)
Many factors contribute to the growing obesity epidemic, but snacking is a huge one. Snacking needs to be addressed. Significant innovation is also needed so physicians can help patients manage their weight.